ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШӘРЬЯР» ҲӘМ ТӘЛИМ - ТӘРБИЯНЫҢ ГЕЙПАРА МӘСЕЛЕЛЕРИ - Пазылов, А.К.; Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study and analysis of the issues of education and upbringing in folklore, in the Karakalpak folk epos «Shariyar», in particular. On the concrete examples the author shows how the issues of moral, labour and ecological education, science, education and pedacocical ideas are reflected in the epos, and their role and importance in educational process today.
Keywords: қорақалпоқ халқ достони «Шарьяр»; этнопедагогика; таълим-тарбиявий фикрлар; одоб-ахлоқ тарбиясы; меҳнат тарбияси; экологик тарбия; илм-фан масалалари; дидактик масалалар